Effect of Zr on precipitation kinetics of Fe-Cr-Al alloys - Ben Niu; Zhenhua Wang; Qing Wang; Sen Ge; Chuang Dong; Ruiqian Zhang (Heat Treatment and Surface Engineering)
The present work investigated the effect of Zr on the precipitation behavior and mechanical properties of Fe-13.5Cr-4.73Al-2.07Mo-(0.34∼0.45)Nb-(0.65∼0.87)Ta-(0.11∼0.33)Zr (wt. %) alloys. The sheet samples were solution treated at 1473 K for 2 h, and then aged at 1073 K for 0∼24 h. The results show that the addition of Zr significantly refines the grains, postpones the precipitation of Laves phase particles, shifts the precipitation kinetics curve to the right, and prolongs the incubation period of phase transformation. At the same time, the low diffusion coefficient of Zr also delays the coarsening rate of precipitated particles. And the yield strength of 0.1Zr alloy (σYS = 418 MPa, δ = 10%) is significantly higher than that of 0.3Zr alloy (σYS = 375 MPa, δ = 6%), exhibiting more prominent mechanical properties.